2017
DOI: 10.1007/s10802-017-0264-y
|View full text |Cite
|
Sign up to set email alerts
|

DRD4 Variants Moderate the Impact of Parental Characteristics on Child Attention-Deficit Hyperactivity Disorder: Exploratory Evidence from a Multiplex Family Design

Abstract: Parental ADHD symptomatology and related impairments have been robustly associated with youth ADHD across decades of work. Notably, these factors may impede typical development of child self-regulation capabilities through both neurobiological and interpersonal processes. High heritability of estimates for the disorder further suggest that these effects are likely genetically-mediated, at least in part. Variation within the dopamine D4 receptor gene (DRD4) has been shown to moderate parental influences on yout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
(89 reference statements)
0
8
0
Order By: Relevance
“…Again, if passive genetic correlation was explaining the results, this longitudinal predictive pattern would not be seen. Third, in a direct test for passive gene-environment correlation, Nikolas and Momany (2017) found no associations of variations in a specific candidate gene for ADHD symptoms (i.e., dopamine receptor 4), and variation in parenting behaviors. Fourth, Wymbs et al (2017) used an experiment involving Bconfederate^child actors who played the role of a child with or without ADHD symptoms during observed interaction with couples (Wymbs et al 2017).…”
Section: Family Diversification Of Adhd Symptoms: Gene-environment Prmentioning
confidence: 90%
See 2 more Smart Citations
“…Again, if passive genetic correlation was explaining the results, this longitudinal predictive pattern would not be seen. Third, in a direct test for passive gene-environment correlation, Nikolas and Momany (2017) found no associations of variations in a specific candidate gene for ADHD symptoms (i.e., dopamine receptor 4), and variation in parenting behaviors. Fourth, Wymbs et al (2017) used an experiment involving Bconfederate^child actors who played the role of a child with or without ADHD symptoms during observed interaction with couples (Wymbs et al 2017).…”
Section: Family Diversification Of Adhd Symptoms: Gene-environment Prmentioning
confidence: 90%
“…This approach has been used widely in epidemiological studies, especially those striving to identify rare genetic variants of large effect size for discrete diseases and disorders (e.g., Hopper et al 2005). The Nikolas and Momany (2017) paper in the current section provides a version of this kind of approach using examination of genotypes in multiple family members. As a general analytic approach, such measurement scaling and analytic methods might be useful for any family-based studies of dyads, triads or beyond.…”
Section: Families and Adhd Symptoms As Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the family environment, young children with the DRD4 7-repeat allele have been shown to be more sensitive to both positive and negative aspects of parenting [33,35]. Another study, focusing on negative family influences, showed that children's DRD4 variants moderated the association between parental inconsistent discipline and the children's ADHD [36]. In relation to the school environment, genetic moderation studies with the DRD4 genotype have examined the influence of peers and teachers in promoting positive development.…”
Section: Introductionmentioning
confidence: 99%
“…Reflecting the known genetic nature of ADHD, two papers (Auerbach et al 2017;Nikolas and Momany 2017) were solicited which incorporate the contributions of both genetic and environmental factors and their interaction in understanding parental ADHD in relation to child ADHD. Three papers examine parental ADHD and/or depression in relation to parenting or child outcomes.…”
mentioning
confidence: 99%